VAMOS HACKEAR A EDUCAÇÃO?: a educação hacker como uma proposta para formação docente. - BARATINHA, Amanda dos Santos (2024)
The present text aims to analyze the contributions/reflections of hacker education in the teacher training process based on the previous survey on remote teaching at the Federal University of Pará/Campus de Breves. The guiding question of the research was to understand what the contribution of hacker education is to teacher training? Thus, literature review and documentary research were used as research instruments. As a contribution to the literature review, the following theorists were used: Himanen (2001), Aguado (2015, 2016, 2018), Lévy (1998, 1999), Freire (1967, 1989, 1992, 1996), Saviani (1989, 1997), and Joye, Moreira and Rocha (2020). In the documentary research, two reports were used, prepared in 2020, on the limits and possibilities of remote teaching in the context of the Marajó-Breves Campus. Finally, it is concluded that hacker education can instigate teacher training from the perspective of hacker ethics, which is fundamental for a society of creative, innovative and proactive subjects.